FORMULASI SEDIAAN LOTION EKSTRAK DAUN JAMBU BIJI (Psidium guajava L) - Tika Romadhonni; Rini Prastyawati; Efrika Alfatheana; Herlando Sinaga (Jurnal Biogenerasi, 2022)
Lotion is a cosmetic preparation in the form of a liquid emulsion that is used on the hands and body with the aim of moisturizing and softening the skin. Guava leaves (Psidium guajava l.) contain natural flavonoids and phenolic compounds that can act as antioxidants and help protect the body. This study aims to determine the best formula for Guava Leaf Extract Lotion. The active ingredient was taken from guava leaf extract. The formulation was carried out with a concentration of 6% by varying TEA FI 2%, FII 2.5%, and FIII 3%. To get the best formula, observation evaluation, organoleptic test, pH test, homogeneity test, spreadability test, adhesion test, irritation test, and stability test were carried out. The results showed that the best formula for lotion preparation of guava leaf ethanol extract with a concentration of 6% was FI thick, light brown, pH 6.5, spreadability of 5.5 cm, adhesion of 4.93 seconds, no irritation, homogeneous and stable at a certain temperature.